Fasiglifam (TAK-875): Mechanistic Investigation and Retrospective Identification of Hazards for Drug Induced Liver Injury. (16th February 2017) - Otieno, Monicah A; Snoeys, Jan; Lam, Wing; Ghosh, Avi; Player, Mark R; Pocai, Alessandro; Salter, Rhys; Simic, Damir; Skaggs, Hollie; Singh, Bhanu; Lim, Heng-Keang
Abstract: TAK-875, a GPR40 agonist, was withdrawn from Phase III clinical trials due to drug-induced liver injury (DILI). Mechanistic studies were conducted to identify potential DILI hazards (covalent binding burden (CVB), hepatic transporter inhibition, mitochondrial toxicity, and liver toxicity in rats) associated with TAK-875. Treatment of hepatocytes with radiolabeled TAK-875 resulted in a CVB of 2.0 mg/day, which is above the threshold of 1 mg/day considered to be a risk for DILI. Covalent binding to hepatocytes was due to formation of a reactive acyl glucuronide (AG) and, possibly, an acyl-CoA thioester intermediate. Formation of TAK-875AG in hepatocytes and/or in vivo was in the order of non-rodents > human ( in vitro only) > rat. These data suggest that non-rodents, and presumably humans, form TAK-875AG more efficiently than rats, and that AG-mediated toxicities in rats may only occur at high doses. TAK-875 (1000 mg/kg/day) formed significant amounts of AG metabolite (≤32.7 μM) in rat liver that was associated with increases in ALT (×4), bilirubin (×9), and bile acids (×3.4), and microscopic findings of hepatocellular hypertrophy and single cell necrosis. TAK-875 and TAK-875AG had similar potencies (within 3-fold) for human multi-drug resistant associated protein 2/4 (MRP2/4) and bile salt export pump, but TAK-875AG was exceptionally potent against MRP3 (0.21 μM). Inhibition of MRPs may contribute to liver accumulation of TAK-875AG. TAK-875 also inhibited mitochondrial respiration in HepG2 cells, and mitochondrial Complex 1 and 2 activities in isolated rat mitochondria. In summary, formation of TAK-875AG, and possibly TAK-875CoA in hepatocytes, coupled with inhibition of hepatic transporters and mitochondrial respiration may be key contributors to TAK-875-mediated DILI.